2016
DOI: 10.1177/2167696816665055
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Adults’ Self-Identified Peer Crowd Affiliations, Risk Behavior, and Social–Emotional Adjustment in College

Abstract: Although peer crowd affiliations have been studied extensively in adolescence, less is known about the crowd structure of emerging adults. The current study tested whether college students' self-reported crowd affiliations were uniquely associated with a broad range of adjustment indices. Participants were 588 emerging adults at a small liberal arts college in the Western United States (M age ¼ 20.07, SD ¼ 1.34; range ¼ 18-26; 411 women). Exploratory factor analysis revealed that the peer crowds examined were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Whilst effective for containing outbreaks, disrupted habits involving strict isolation measures can adversely affect both physical and mental health, with potentially exacerbated effects among young adults who rely upon positive peer interactions for their general wellbeing [ 4 , 5 ]. Likely consequences of home isolation are changes to eating and physical activity behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst effective for containing outbreaks, disrupted habits involving strict isolation measures can adversely affect both physical and mental health, with potentially exacerbated effects among young adults who rely upon positive peer interactions for their general wellbeing [ 4 , 5 ]. Likely consequences of home isolation are changes to eating and physical activity behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that identification with peer crowds is common among young adults 25 and continues to have significant associations with risk behaviors and indicators of emotional well-being. 26,27 Much work in this area has been done among college students. 5,25,28,29 Kuh and colleagues 30 describe typologies of college students based on factors, such as involvement in academics, sports/recreation, arts/music, and social activities.…”
Section: Introductionmentioning
confidence: 99%
“…5,25,28,29 Kuh and colleagues 30 describe typologies of college students based on factors, such as involvement in academics, sports/recreation, arts/music, and social activities. Hopmeyer et al 26,31 extended this line of work by developing the College Peer Crowd Questionnaire and identified four broad crowds: social, counterculture (akin to alternative), scholastic (akin to academics), and athletic (akin to jocks).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer crowd affiliation was measured using a modified, 19-item version of the College Peer Crowd Questionnaire (Hopmeyer & Medovoy, 2016; based on La Greca, Prinstein, & Fetter, 2001), which was adapted to reflect the school-specific peer crowds that were uncovered during the focus group portion of the procedure. An example item is: “How strongly do you affiliate with the ravers at this university?” For each item, students were also provided with a short description of the crowd.…”
Section: Methodsmentioning
confidence: 99%